Validation and reliability of the Malaysian English version of the psychosocial impact of dental aesthetics questionnaire for adolescents - Wan Hassan, Wan Nurazreena; Mohd Yusof, Zamros Yuzadi; Makhbul, M.Z.M.; Shahidan, S.S.Z.; Mohd Ali, S.F.; Burhanudin, R.; Gere, M.J. (BioMed Central, 2017)
Background: The Malay version of the Psychosocial Impact of Dental Aesthetics Questionnaire has been validated for use by Malaysian adolescents. Although Malay is their national language, English is widely used as the lingua franca among Malaysians of different ethnicities. This study aimed to validate an English version of the PIDAQ adapted for use by Malaysian adolescents to optimize data capture from adolescents who prefer English as the medium for communication.